Enhancing Reflective Writing through E-Learning in Undergraduate Medical Education - Nurulhuda, Mat Hassan; Siti Norazlina, Juhari; Harmy, Mohamed Yusoff; Norwati, Daud; Hassan Basri, Mukhali (2017)
E-learning in medical education in Universiti Sultan Zainal Abidin is still considered to be in an infancy stage. Although E-learning tools have been used in many settings for quite a long time (1), previous evidence of their use and effectiveness in the pre-service education of medical professionals in low and middle income countries is limited (2). Reflective learning and practice is an important tool in the practice of medicine and are central to medical education and a career in medicine (3, 4).